Inflammatory profile associated with insulin resistance in non-overweight versus overweight people living with HIV in Pune, Western India. Issue 7 (July 2022) - Chebrolu, Puja; Sangle, Shashikala; Nimkar, Smita; Salvi, Sonali; Chavan, Amol; Kulkarni, Vandana; Shere, Dhananjay; Deshpande, Prasad; Brown, Todd T.; Mathad, Jyoti S.; Marbaniang, Ivan; Mave, Vidya
Abstract: Background: People living with HIV have greater diabetes (T2DM) than the general population despite lower prevalence of overweight/obesity. Both insulin resistance (IR), a T2DM precursor, and HIV are independently associated with chronic inflammation. Inflammation may be a pathophysiological link explaining IR in people living with HIV who are not overweight but is not well understood. Aims: To study the association between inflammation and IR in non-overweight and overweight people living with HIV. Methods: In a cohort of adult people living with HIV with undetectable viral load in Pune, India, we measured fasting insulin, glucose, and 9 inflammatory markers. IR was defined as HOMA-IR ≥2, and non-overweight as BMI ≤23 kg/m 2 . We used modified Poisson regression to evaluate the association between inflammatory markers and IR in overweight and non-overweight. Results: Of 288 participants, 66% (n = 189) were non-overweight. Among non-overweight, prevalence of IR was 34% (n = 65). Each doubling of MCP-1 and leptin was associated with IR on univariate analysis (prevalence ratio (PR) 1.29, 95%CI 1.07–1.53, p < 0.01; PR 1.13 95%CI 1.01–1.26, p = 0.03). Leptin remained associated with IR after adjustment for age, MCP-1, gender, cholesterol, and waist circumference (adjusted PR 1.20 95%CI 1.06–1.36, p < 0.01). Among overweight, prevalence of IR was 69% and no markers were associated with IR. Conclusions: One in 3 non-overweight people living with HIV in India with controlled viremia have IR. Leptin was associated with IR among non-overweight people living with HIV and may provide insight into the pathophysiology of metabolic disease in this population. Highlights: One in 3 non-overweight people living with HIV in India with controlled viremia had insulin resistance Leptin was associated with insulin resistance among non-overweight people living with HIV after adjustment for other risk factors No inflammatory markers were significantly associated with insulin resistance among the overweight group